Detection of Brucella S2 vaccine strain by a loop-mediated isothermal amplification (LAMP) method - Mu, Jiaming; Li, Qi; Yan, Xu; Mao, Xiaowei; Shi, Yaqin; Qin, Yun; Liu, Chunxia; Wang, Wenlong (Frontiers in Cellular and Infection Microbiology, 2022)
Brucellosis is a highly prevalent zoonotic disease caused by Brucella spp. Brucella suis S2 vaccination is an effective strategy to prevent animal brucellosis. However, S2 induces antibodies against the smooth lipopolysaccharide, making it challenging to distinguish field infected from vaccinated livestock. Early and accurate diagnosis is essential for infection control and prevention. In this study, we aimed to develop a quick and accurate assay to distinguish the Brucella S2 vaccine strain from closely related B. abortus and B. melitensis. Whole-genome sequencing of B. suis S2 was performed, and the sequence was compared with that of the genomes of B. abortus and B. melitensis. One specific gene, GL_0002189, was selected as a marker to differentiate the Brucella S2 vaccine strain from B. abortus and B. melitensis. A loop-mediated isothermal amplification (LAMP) assay was developed, based on the GL_0002189 gene, and then assessed for target specificity, lower limit of detection, and repeatability. Our results revealed that there was no cross-reaction with other strains, and the LAMP assay displayed high sensitivity for detecting S2 with a minimum detection limit of 18.9×103 copies/µL DNA input, it is nearly 100 times higher than conventional PCR technology. Concordance between the LAMP assay and a conventional polymerase chain reaction method was assessed using 54 blood samples collected from sheep with suspected brucellosis. Total concordance between the two assays was 92.6%, without a significant difference (p > 0.05) in the test results. This is the first report of a LAMP assay for the detection of the B. suis S2 vaccine strain. Our approach can be helpful for the control and eradication of brucellosis, and its simplicity in requiring no specialized equipment or personnel makes it useful for implementation in resource-limited settings as well as for field use.